Social Justice Education as an Intercultural Experience for Foreign Students in the United States - Ellen Yeh; Yonty Friesem (The EUROCALL Review, 2024)
Many language learners struggle with unequal access and lack of opportunities for active participation in meaningful discussions in and outside of the classroom. In this study, 15 international college students engaged in critical media literacy discussion over a myriad of social justice topics through the lens of intercultural understanding and acceptance. Participants analyzed the content and recorded video reflection on an online video discussion platform, Flipgrid as they answer the five critical media literacy questions. These critical questions foster discussions of intercultural interpretation online and in class discussions as students expressed their perceptions of social justice issues. This project drew on the theory of intercultural communicative competence (Byram, 1997) integrating social justice into language curriculum in two ways: by exposing students to important issues, and by helping students claim their voice in the discussion. Results of students’ video reflections and face-to-face discussions show the trajectory and growth of students’ progress in intercultural awareness. The findings offer guidelines for language educators to incorporate issues of social justice by using engaging platforms and media literacy practices.